(3efXhQ QjGOj JcfhdhLjs - (3eRgQ TYHGf(B, (3GdYGfjs; (3Thbj fGLj LhGO(B, (3MSjf YdjGf GQTjOs ((3YeGf(B:s (3OGQ UaGA(B,s, 2009)
(3GdQjGOI , eOGNd OQGSI GdQjGOI, GSJQGJjLjI GdQjGOI , GdGTcGd GdbGfhfjI , OQGSI GdLOhi , GOGQI GdJehjd , GdJNWjW GdGSJQGJjLj , GOGQI GdeNGWQ h GdJCejf , GOGQI GdTQGA , GOGQI GdeNRhf h JNWjW GdGMJjGLGJ aj GdeTQhYGJ GdUZjQI , GdeTQhYGJ GdUZjQI GdGdcJQhfjI , GdJfHD HGdeHjYGJ , GdJSYjQ , GdGYdGf h GdJQhjL , GdaQU GdYGdejI h GdeSDhdjI GdGNdGbjI h GdGLJeGYjI ddeTQhYGJ GdUZjQI (B.s
(3eQGLY U(B.337 (3; bGFeI GdeUWdMGJ U(B.303 (3; LOGhd U(B.14 (3;GTcGd U(B.15s
Keywords: (3GdeTQhYGJ `` GOGQIs; (3GdeTQhYGJ GdUZjQIs; (3JfajP GdeTGQjYs